Platelet haemostasis during the menopausal period - Stachowiak, Grzegorz; Zając, Agnieszka; Pertyński, Tomasz (Menopause Review/Przegląd Menopauzalny, 2008)
This article is a review of the current data on: 1) the role of platelets in the female circulatory system, 2) alterations in platelet haemostasis during the menopausal period, and 3) the influence of hormone therapy (HT) on platelet functions. Reversal of postmenopausal changes in platelet haemostasis by some types of HT seems to be one of the important elements of this therapy, supporting the fact that HT, when administered properly, cannot increase the risk of cardiovascular diseases but acts as a cardioprotective factor.